Discourse Analysis and Comparison of Jane Austen’s Pride and Prejudice and Charlotte Brontë’s Jane Eyre : Social Class, Social Mobility and What Society Expects of Women - Kopani, Siria (My University, 2024)
As my thesis topic, I decided to research, analyse and compare the two classic novels: Pride and Prejudice by Jane Austen and Jane Eyre by Charlotte Brontë. The foci of this analysis will be the attitudes of the novels' protagonists on social class, the concept of social mobility and women's rights during the eighteenth and nineteenth centuries. As a method of choice for my thesis, I chose close reading. I chose these novels as primary sources and previous studies as secondary sources order to back up my claims further. I will subsequently compare the two novels focusing on characterization, how the two protagonists perceive the world around them and what paths do they follow when moving on to upwards social mobility. I will then compare the treatment of social class as a theme, looking into the way Austen and Brontë criticize society and support women's rights in a society that was reluctant to do so. The thesis is concluded with me acknowledging the different styles of the authors, the criticism they address towards society and its’ way of thinking, along with the protagonists' efforts to support themselves and move up in social class.

Tutkimuksen tarkoituksena on tutkia, analysoida ja verrata kahta romaania: Jane Austenin Ylpeyttä ja ennakkoluuloa ja Charlotte Brontën Kotiopettajattaren romaania. Tässä analyysissa keskityn päähahmojen asenteisiin sosiaalista luokkaa kohtaan, sosiaaliseen liikkuvuuteen käsitteenä ja naisten toimijuuteen 1800- ja 1900-luvulla. Valittuna tutkimuksen menetelmänä oli lähiluku, joka viittaa kirjallisten tekstien ja niiden muunlaisten kohtien tarkkaan analyysiin ja tulkintaan. Käytin romaaneja primäärilähteinä ja edellisiä tutkimuksia sekundaarilähteinä tukeakseni väitteitäni. Analysoituani kaksi valitsemaani romaania erikseen, vertailen päähahmojen maailmankatsomuksia, eli miten he hahmottavat yhteiskuntaa. Keskityn myös tapoihin, joilla he hakevat sosiaalista liikkuvuutta. Sitten vertailen, miten Austen ja Brontë kirjoittavat sosiaalisesta luokasta. Vertailen myös, miten kirjailijat kritisoivat yhteiskuntaa, tarkastellen millä tavoilla he tukivat naisten oikeuksia silloin, kun ne eivät olleet tärkeitä yhteiskunnan silmissä. Tutkimuksen lopussa huomioin kirjoittajien kirjoitustyylien väliset erot, heidän asenteensa yhteiskuntaa kohtaan, sekä päähahmojen ponnistelut heidän yrittäessä selviytyä eteenpäin yhteiskunnassa.
Keywords: Jane Austen, Charlotte Brontë, social class, social mobility, yhteiskuntaluokka, sosiaalinen liikkuvuus